The right to life, constitutional principles and an interpretation by values - Calabrò, Gian Pietro (Medicina e Morale, 1997)
The article aims to show the role that the right to life, in its axiologic perspective, can play within the legal system of constitutional democracies. There is a close connection between life and the notion of the person and the latter is placed in the centre of the constitutional system. In developing some of Antonio Baldassarre's considerations on the need for the life value to be balanced by an equal value, the author proposes the possibility of establishing a hierarchy within the so called interpretation by values, which has at the top, the right to life as the precondition of any other right. In this perspective the right to life deeply affects the destiny of pluralistic democracies and becames the principle of their legitimation. In other words, the author concludes that the right to life can be understood as the Grundnorm without, however, being taken in a hypothetical and conventional way according to the kelsenian plan, and thus qualifies the whole system from a juridical and ethical point of view.